Faktor Prediktor Pertumbuhan Anak Usia 12-23 Bulan di Kecamatan Limo Kota Depok - Elmina Tampubolon (Jurnal Kesehatan Komunitas, 2021)
The growth and development of infancy determine the growth and subsequent development until adulthood. Several studies show that a mother's knowledge is the main predictor of child growth, but there are still few studies that examine other predictor variables of child growth. This study aims to analyze the predictor factors of the growth of children aged 12-23 months in Limo District, Depok City. This type of research is quantitative analytic. The quantitative design used is a case-control study. The research sample was all mothers who had children under the age of 12-23 months, consisting of 53 children in the case group and 53 children as controls. The sampling technique was carried out by purposive sampling. Bivariate analysis using chi-square test, t-independent test, and Mann-Whitney. Multivariate analysis using multiple logistic regression tests. The results of the analysis showed that supplementary feeding and frequency of feeding were predictors of growth in children aged 12-23 months. Suggestions to the Ministry of Health and health workers at Primary Health Care to strengthen educational programs about providing quality complementary food or complementary foods and if necessary, providing additional milk to prevent stunting in children.